2007
DOI: 10.1007/s11142-007-9060-1
|View full text |Cite
|
Sign up to set email alerts
|

Accounting conservatism and corporate governance

Abstract: We predict that firms with stronger corporate governance will exhibit a higher degree of accounting conservatism. Governance level is assessed using a com posite measure that incorporates several internal and external characteristics. Consistent with our prediction, strong governance firms show significantly higher levels of con ditional accounting conservatism. Our tests take into account the endogenous nature of corporate governance, and the results are robust to the use of several measures of conservatism (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
191
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(216 citation statements)
references
References 83 publications
(136 reference statements)
19
191
2
4
Order By: Relevance
“…If the corporate governance is better, the need for accounting conservatism is lower. However, the findings obtained by Lara, Osma and Penalva (2009) show when the corporate governance mechanism is better, accounting conservatism increases, and there exists a causal relationship. Ramalingegowda and Yu (2012) anticipate and find that if the institutional investors with the motivation to exercise supervision hold more shares, the firms will be more inclined to adopt the conservative accounting principle.…”
Section: Accounting Conservatismmentioning
confidence: 94%
See 1 more Smart Citation
“…If the corporate governance is better, the need for accounting conservatism is lower. However, the findings obtained by Lara, Osma and Penalva (2009) show when the corporate governance mechanism is better, accounting conservatism increases, and there exists a causal relationship. Ramalingegowda and Yu (2012) anticipate and find that if the institutional investors with the motivation to exercise supervision hold more shares, the firms will be more inclined to adopt the conservative accounting principle.…”
Section: Accounting Conservatismmentioning
confidence: 94%
“…For example, Lee and Yeh (2004) argue that the worse the corporate governance mechanism is, the higher will be the probability of financial distress. Besides, Lara, Osma and Penalva (2009) predict that the degree of accounting conservatism is higher when the corporate governance is better. From the above study, it can be found the corporate governance can affect accounting conservatism and financial distress simultaneously, and corporate governance can be viewed as a generalized firm characteristic.…”
Section: Accounting Conservatism and Financial Distressmentioning
confidence: 99%
“…Garcia Lara et al (2009) confirm that stronger corporate governance will present a higher degree of accounting conservatism. However, Chi and Hsu (2009) confirm that firms with weaker governance structures tend to be more conservative.…”
Section: Corporate Governance Variablesmentioning
confidence: 82%
“…Chen et al 2011 [20] analyzed the effects of overinvestment and underinvestment on the quality of earnings for private firms in emerging markets. Similarly, Garcia-Lara et al (2010) [41] reported that conservatism in accounting can reduce both overinvestment and underinvestment. This implies that the conservativeness of the accounting process reduces the investment cash flow of overinvested firms and facilitates the access of external funds for underinvestment firms.…”
Section: Earnings Management and Investment Efficiencymentioning
confidence: 95%